Morfologia, fenologia e resistência de Amaranthus spp. - Trevizan, Katia (2020)
The inadequate use of weed management methods has led to the selection of herbicide resistant species. Among these, there is “caruru” with several species of Amaranthus: A. viridis; A. lividus; A. spinosus; A. hybridus and A. retroflexus. The population of resistant individuals rises due to the lack of control that allows the fruiting and dissemination of seeds. This study has as general objective to characterize the morphology and phenology, as well as to identify if there is formation of viable hybrids from the intraspecific and interspecific crossing of species of carurus. It is assumed that if there is formation of viable hybrids from the crossing between resistant and susceptible biotypes to imazetapir, in Amaranthus spp, then resistant and susceptible individuals will be observed in the progeny when susceptible biotype plants are manually pollinated with pollen from resistant plants, under controlled conditions. To this end, research began in 2017, with the collection of seeds from different locations, and from then on a series of experiments were conducted in a greenhouse and laboratory. Germination and dormancy of Amaranthus spp seeds were tested; characterization of the morphological development of the Amaranthus spp root system; description of the morphology and phenology of species of Amaranthus spp; dose-response curves and the effectiveness of the herbicide imazetapyr on different species of Amaranthus; transfer of resistance of A. retroflexus to the herbicide imazetapir by crosses. Conclusions were obtained that: 1) dormancy is overcome for A. viridis associating the lack of light with mechanical scarification; 2) A. lividus prolonged imbibition and mechanical scarification without the presence of light; 3) A. spinosus mechanical scarification in both light situations; A. hybridus did not respond to any of the treatments; A. retroflexus biotype susceptible to mechanical scarification and prolonged imbibition, associated with lack of light; A. retroflexus biotype resistant to prolonged imbibition associated with the presence of light; The dichotomous image key helps the producer to identify Amaranthus species at field level. The A. retroflexus biotype susceptible to imazetapyr accumulated a greater amount of dry mass, mainly in the stems and flowers, followed by A. hybridus, A. spinosus, A. viridis, A. retroflexus resistant biotype and A. lividus. The root system of A. spinosus has a higher root volume than the others followed by the susceptible A. retroflexus biotype ≥ A. hybridus ≥ A. viridis ≥ A. lividus≥ A. retroflexus resistant biotype. There is a variation in susceptibility among Amaranthus species: A. viridis, A. lividus, A. hybridus, A. spinosus and A. retroflexus. Amaranthus viridis, A. lividus, A. hybridus, A. spinosus and the A. retroflexus biotype from Passo Fundo are efficiently controlled with lower doses than the registration. The biotype of A. retroflexus from Lucas do Rio Verde - MT is resistant to the herbicide imazetapyr. There was no interspecific hybridization between the five species tested. However, intraspecific hybridization was found among A. retroflexus biotypes, so the hypothesis raised by this study is not true.